Influência da luminosidade na germinação e desenvolvimento inicial do piquiá Caryocar villosum (Aubl.) Pers. (Caryocaraceae) - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2023)
A specie emerging in the Amazon rainforest, the piquiá Caryocar villosum (Aubl.) Pers, has wide and recognized ecological, economic and social utility, thus, the species has been exploited to exhaustion, with risk of extinction due to the difficulty of natural regeneration in its natural habitat, being a demanding heliophile, it needs clearings for its better development in forest dynamics being, which is why the present study is proposed when evaluating the importance of sunlight in seed germination and initial development of plants of the species Caryocar villosum. For this, the seeds were collected and prepared for photoblastic germination in two modes of luminous intensity: lot in full sun and, lot under shading at 50% light blocking covering with sombrite-type screen®, resembling the forest environment. The seedlings were filled in appropriate bags, and kept in the sun and shade. Germination percentages were recorded and seedling development was measured in both lots. At the end of the experiment, calculations were performed with the collected data, noting that direct illumination of the sun was not important to impose quantitative difference in the viability of the seeds, although it influenced to shorten germination. Related to the initial development, direct light proved to be important to determine a higher average growth in height and mainly to impose a large difference in the volume of final living biomass accumulated in the stem of plants grown in the full sun treatment.
Keywords: Caryocar villosum; Germinação; Desenvolvimento; Intensidade de luz; CNPQ:: CIÊNCIAS BIOLÓGICAS